Evaluation of Retention among Acid-etch and Self-etch Sealants: An in vivo Study (Journal of Orofacial Research, 1970)
Aim: The aim of the study is to evaluate the retention of fissure sealants following the use of self-etch priming agent and traditional acid-etch method. Materials and methods: Thirty subjects around the age 8 to 12 years old school children was recruited to this study by two dental professionals. Paired lower molars were the principal unit of analysis. Pit and fissure sealant placement lower molars followed by traditional acid-etching done on 36 and self-etch primer (3M ESPE) on 46. After 6 months the retention was evaluated using Smales RJ and Wong KC (1999) retention evaluation criteria. The Chi-square test was used to evaluate the difference in the retention rates. Results: The total retention in the self-etch sealant group seems to be high, the difference between the groups was not statistically significant. The chi-square computed value was found to b e c2 = 0.417, df = 1 and p = 0.519. This means that there was no significance difference between the retention rate of self-etch sealant compared to conventional acid-etch technique. Hence, this study conclude that self-etch primer (3M ESPE Adper) is effective in bonding sealant to enamel and that the simplified method dramatically shortens treatment time and treatment complexity.